Relationship between atmospheric blocking and cold day extremes in current and RCP8.5 future climate conditions over Japan and the surrounding area. (7th November 2016) - Kitano, Yoshikazu; Yamada, Tomohito J.
Abstract: Atmospheric blocking is one of the most impactful weather patterns in midlatitude regions, causing floods, droughts and unusually high or low temperatures. This study investigates the relationship between extremely cold days over Japan and its surroundings and North Pacific blocking in the European Centre for Medium‐range Weather Forecasts (ECMWF) re‐analysis (ERA‐40), phase 5 of the Coupled Model Intercomparison Project (CMIP5) for historical weather and the representative concentration pathway 8.5 (RCP8.5) experiments based on nine climate model datasets in the boreal winter season. Under the climate change conditions based on the RCP8.5 future scenario, extreme cold days (i.e. the first percentile of cold days) over Japan and its surroundings will become weaker but occur more widely when blocking is generated over the northwestern Sea of Okhotsk and its surroundings, because the blocking frequency over this area will decrease and the intensity will weaken.